White Paper of the Society of Computed Body Tomography and Magnetic Resonance on Dual-Energy CT, Part 2: Radiation Dose and Iodine Sensitivity. Issue 6 (November 2016) - Foley, W. Dennis; Shuman, William P.; Siegel, Marilyn J.; Sahani, Dushyant V.; Boll, Daniel T.; Bolus, David N.; De Cecco, Carlo N.; Kaza, Ravi K.; Morgan, Desiree E.; Schoepf, U. Joseph; Vrtiska, Terri J.; Yeh, Benjamin M.; et al.
Abstract : Abstract: This is the second of a series of 4 white papers that represent Expert Consensus Documents developed by the Society of Computed Body Tomography and Magnetic Resonance through its task force on dual-energy computed tomography. This paper, part 2, addresses radiation dose and iodine sensitivity in dual-energy computed tomography.